HISTOPATOLOGI HATI DAN JANTUNG IKAN NILA (Oreochromis niloticus) YANG DIINFEKSI Aeromonas salmonicida subsp. achromogenes ISOLAT BALI DAN DIOBATI DENGAN ENROFLOKSASIN - , MUHAMAD RIZKY PUTRA, Prof. drh. Kurniasih, MVSc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Aeromonas salmonicida is normal bacteria in the water around the world but the existence of it often makes fish mortality. The purpose of this study was to find out histopathological changes of liver and heart of tilapia caused by Aeromonas salmonicida infection and the changes after getting treated with enrofloxacin. Six fishes as the samples were injected by Aeromonas salmonicida 0,1cc x 10Â¹Â³ cell/ml in intraperitoneal. Three fishes were left post infection until it died and being necropsied. Three other were cured by enrofloxacin 10 mg/kg intraperitoneal once after a week post infection and being necropsied. Liver and heart were used as histopathology preparation sample. The result showed pathologic changes were inflammation in epicardium and endocardium, degeneration vacuolization and hepatitis in liver. Meanwhile, the liver and heart of fish that treated with enrofloxacin was normal yet still found several degeneration. The treatment with enrofloxacin is good to treat Aeromonas salmonicida infection.